PROPRIEDADES TECNOLÓGICAS DA MADEIRA JOVEM DE ANGICO VERMELHO E SUA EFICIÊNCIA EM JUNTAS COLADAS - Silva, Emilly Soares Gomes da (2021)
The objective of the study was to characterize the physical and mechanical properties of young wood of red-angico and to evaluate the performance of the species in the bonding of pieces with different commercial adhesives. The characterization of the properties of the wood was carried out on thinned trees from the 3 m × 3 m, 4 m × 4 m e 5 m × 5 m spacing. The physical properties were determined in terms of basic density, linear and volumetric retractability, and degree of collapse of the wood in the base-top and pith-bark directions. The mechanical properties were determined according to the shear strength, resistance to parallel and perpendicular compression to the fibers, resistance to static bending and Janka hardness. For wood bonding, the adhesives urea-formaldehyde, vinyl polyacetate, resorcinol-formaldehyde and tannin urea-formaldehyde in the proportion 20:80 (tannin:urea) were used, which were characterized, and then glued in the weights of 200, 250, 300 and 350 g m-2 . The glued joints were pressed at environmental temperature and tested to determine the shear strength in the glue line. The percentage of flaws and wood chemistry were determined in order to assess the interaction of wood with adhesives. The results demonstrate that the physical-mechanical properties of the red-angico were superior in wood from the two largest spacings, presenting better resistance and rigidity. The significant trends observed in the pith-bark direction checked an instability of the wood closer to the pith due to a higher proportion of juvenile wood, and it is recommended to exploration the wood in the most peripheral regions of the log. Generally speaking, plantig spacing and thinning did not negatively affect the quality of red-angico wood. In relation the gluing efficiency, it was observed that there was not a satisfactory adhesion between the wood and the different adhesives glued in the different weights. The average values of shear strength in the glue line were below what is recommended for commercial use. The content of extractives and the density of the wood associated with the viscosity of the of the adhesives promoted an insufficient interconnection, generating glued pieces of inferior quality. The failure percentage was below the recommended 60%, reinforcing the observed data for resistance, which indicated the low quality of the glued joints.